All-solid-state battery pole piece and preparation method thereof
By using vertically arranged magnetic composite solid electrolyte fibers in all-solid-state battery poles, the problem of long ion transmission paths under low conductivity and high surface density design of solid electrolyte is solved, and the internal resistance of the battery is reduced and the rate performance is improved.
Patent Information
- Application Number
- CN202510078726.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
Due to the low ion conductivity and long ion transmission paths of solid electrolytes under the design of high surface density, the battery's performance at high magnification is limited and the internal resistance increases.
Magnetic composite solid electrolyte fibers are used, and the arrangement direction of the fibers is perpendicular to the current collector. Compound active material particles and composite solid electrolyte particles are formed by spraying and cooling, and all-solid battery electrode sheets are pressed by multi-roll hot pressing equipment.
It reduces the transmission path of lithium/sodium ions, reduces the internal resistance of the battery, and improves the rate performance and cycle stability of the battery.
Smart Images

Figure CN119852308A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery production, and in particular to a battery pole piece and a preparation method thereof. Background Art
[0002] In the development of modern energy storage technology, all-solid-state batteries have become a research hotspot due to their excellent safety and high energy density. In all-solid-state batteries, ion transport mainly depends on the ionic conductivity of the solid electrolyte (SSE). Compared with traditional liquid electrolytes, SSE generally has lower ionic conductivity, which limits the performance of the battery at high rates. In addition, the transmission path of ions in SSE is affected by the electrode structure, especially under high surface density design, the ions need to travel a longer distance, further increasing the internal resistance of the battery. Summary of the invention
[0003] The purpose of the present invention is to provide an all-solid-state battery pole piece to solve the above technical problems;
[0004] The present invention also aims to provide a method for preparing an all-solid-state battery electrode to solve the above technical problems;
[0005] An all-solid-state battery pole piece, comprising:
[0006] current collector;
[0007] An active material coating is covered on the upper surface and the lower surface of the current collector, wherein the active material coating comprises magnetic composite solid electrolyte fibers, and the arrangement direction of the magnetic composite solid electrolyte fibers is perpendicular to the current collector.
[0008] Preferably, the current collector is one of a positive electrode current collector and a negative electrode current collector;
[0009] The positive electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil;
[0010] The thickness of the positive electrode current collector is 4um to 20um;
[0011] The negative electrode current collector is one of the aluminum foil, the microporous aluminum foil, the corroded aluminum foil, the composite aluminum foil, the copper foil, the microporous copper foil, the corroded copper foil, the composite copper foil, the steel foil, the corroded steel foil and the microporous steel foil;
[0012] The thickness of the negative electrode current collector is 4 um to 15 um.
[0013] Preferably, the active material coating is one of a positive electrode active material coating and a negative electrode active material coating, and the thickness of the active material coating is 10 um to 300 um;
[0014] The active material coating also includes composite active material particles, a conductive agent, composite solid electrolyte particles and a binder;
[0015] The conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene and carbon fibers.
[0016] Preferably, the composite solid electrolyte particles include first type composite solid electrolyte particles and second type composite solid electrolyte particles;
[0017] The magnetic composite solid electrolyte fiber comprises a magnetic nanowire and the second type of composite solid electrolyte particles wrapped outside the magnetic nanowire, and the weight ratio of the magnetic nanowire to the second type of composite solid electrolyte particles is (70:30) to (90:10);
[0018] The particle size D50 of the magnetic composite solid electrolyte fiber is 10nm to 50nm, and the length of the magnetic composite solid electrolyte fiber is 1um to 200um;
[0019] The magnetic nanowires include at least one of ferrite nanowires, cobalt-based nanowires, nickel-based nanowires, tubular carbon nanofibers, and CaO / α-Fe nanocomposite fibers.
[0020] Preferably, the mass ratio of the first type of composite solid electrolyte particles to the second type of composite solid electrolyte particles is (75:25) to (90:10);
[0021] The composite active material particles include active material particles and the second type of composite solid electrolyte particles wrapped outside the active material particles, and the thickness of the second type of composite solid electrolyte particles is 10nm to 50nm;
[0022] The active material particles are one of positive electrode active material particles and negative electrode active material particles, and the mass ratio of the positive electrode active material particles to the second type of composite solid electrolyte particles is (93:7) to (97:3);
[0023] The composite active material particles are one of positive electrode composite active material particles and negative electrode composite active material particles, the particle size D50 of the positive electrode composite active material particles is 3.5um to 5.0um, and the particle size D50 of the positive electrode active material particles is 2.0um to 4.0um;
[0024] The positive electrode active material particles include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, sodium nickel iron manganese copper oxide and Na x At least one of M1[M2(CN)6](0<x<6);
[0025] The negative electrode active material particles include at least one of graphite, silicon, lithium titanate, hard carbon, and soft carbon;
[0026] The first type of composite solid electrolyte particles include inorganic solid electrolyte particles and the second type of composite solid electrolyte particles wrapped outside the inorganic solid electrolyte particles, and the thickness of the second type of composite solid electrolyte particles is 10nm to 50nm;
[0027] The mass ratio of the inorganic solid electrolyte particles to the second type of composite solid electrolyte particles is (85:15) to (95:5);
[0028] The particle size D50 of the first type of composite solid electrolyte particles is 0.3um to 0.5um, and the particle size D50 of the inorganic solid electrolyte particles is 0.2um to 0.4um;
[0029] The second type of composite solid electrolyte particles comprises an inorganic electrolyte salt and an organic polymer solid electrolyte wrapped outside the inorganic electrolyte salt, and the weight ratio of the organic polymer solid electrolyte to the inorganic electrolyte salt is (80:20) to (90:10);
[0030] The particle size D50 of the second type of composite solid electrolyte particles is 0.15um to 0.30um.
[0031] A method for preparing an all-solid-state battery pole piece, used for preparing the all-solid-state battery pole piece, comprising:
[0032] Step S1, spraying and cooling the prefabricated molten slurry to obtain the second type of composite solid electrolyte particles;
[0033] Step S2, adding active material particles to the prefabricated molten slurry, spraying and cooling after mixing to form composite active material particles;
[0034] Step S3, adding inorganic solid electrolyte particles to the prefabricated molten slurry, spraying and cooling after mixing, to form first type composite solid electrolyte particles;
[0035] Step S4, adding magnetic nanowires to the prefabricated molten slurry, spraying after mixing, and stretching and refining under the action of electric field force to form the magnetic composite solid electrolyte fiber;
[0036] Step S5, mixing the second type of composite solid electrolyte particles, the composite active material particles, the first type of composite solid electrolyte particles, the conductive agent and the adhesive according to a first mass ratio, adding the magnetic composite solid electrolyte fiber, mixing again to obtain a mixed material, spraying the mixed material on a substrate, and introducing an electric field to obtain the active material coating;
[0037] Step S6, pressing the current collector and the active material coating at a first temperature and a first pressure by a multi-roll hot pressing device to obtain the all-solid-state battery electrode.
[0038] Preferably, the prefabricated molten slurry in step S1 to step S4 is obtained by melting an organic polymer solid electrolyte in a vacuum melting machine, and then adding an inorganic electrolyte salt and stirring.
[0039] Preferably, in step S5, the first mass ratio is (80:10:5:2:3) to (90:6:2:1:1).
[0040] Preferably, in step S6, the first temperature is 45°C to 100°C, and the first pressure is 5MPa to 100MPa.
[0041] Preferably, in step S6, the multi-roller hot pressing device is provided with n pressing rollers along the first direction, wherein the temperature of the n / 2th pressing roller is the highest, the temperature of the pressing rollers before the n / 2th pressing roller increases successively along the first direction, and the temperature of the pressing rollers after the n / 2th pressing roller decreases successively along the first direction;
[0042] The pressure of the n pressure rollers gradually increases along the first direction;
[0043] Where n∈[6,12] and n is divisible by 2.
[0044] The beneficial effects of the present invention are: it can reduce the transmission path of lithium / sodium ions, thereby reducing the internal resistance of the battery and improving the battery rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a schematic diagram of the structure of the all-solid-state battery pole piece of the present invention;
[0046] Figure 2 is a schematic diagram of a composite active material particle of the present invention;
[0047] Figure 3 is a schematic diagram of the first type of composite solid electrolyte particles of the present invention;
[0048] Figure 4 is a schematic diagram of the second type of composite solid electrolyte particles of the present invention;
[0049] Figure 5 is a schematic diagram of the magnetic composite solid electrolyte fiber of the present invention;
[0050] Figure 6 It is a step diagram of the method for preparing the all-solid-state battery electrode of the present invention.
[0051] In the attached figure: 1. current collector; 2. active material coating; 3. magnetic composite solid electrolyte fiber; 4. magnetic nanowire; 5. composite active material particles; 6. active material particles; 7. first type of composite solid electrolyte particles; 8. inorganic solid electrolyte particles; 9. second type of composite solid electrolyte particles; 10. inorganic electrolyte salt; 11. organic polymer solid electrolyte. DETAILED DESCRIPTION
[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0054] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.
[0055] An all-solid-state battery electrode, such as Figures 1 to 5 As shown, including,
[0056] current collector 1;
[0057] The active material coating 2 covers the upper surface and the lower surface of the current collector 1 . The active material coating 2 includes magnetic composite solid electrolyte fibers 3 . The arrangement direction of the magnetic composite solid electrolyte fibers 3 is perpendicular to the current collector 1 .
[0058] Specifically, the present invention provides an all-solid-state battery pole piece, in which the arrangement direction of the magnetic composite solid electrolyte fiber 3 in the all-solid-state electrode piece is perpendicular to the current collector 1. Under such an arrangement, the movement distance of the sodium / lithium ions in the pole piece during the battery charging and discharging process is the shortest, thereby reducing the battery impedance and improving the battery rate performance.
[0059] In a preferred embodiment, the current collector 1 is one of a positive electrode current collector and a negative electrode current collector;
[0060] The positive electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil;
[0061] The thickness of the positive electrode current collector is 4um to 20um;
[0062] The negative electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil;
[0063] The thickness of the negative electrode current collector is 4um to 15um.
[0064] Specifically, the thickness of the positive electrode current collector is 5um to 12um, and the thickness of the negative electrode current collector is 4um to 10um, which can ensure good electron conduction ability without increasing the overall weight and internal resistance of the battery due to excessive thickness.
[0065] The current collector 1 serves as the main channel for electron conduction and cooperates closely with the vertically arranged magnetic composite solid electrolyte fibers 3 (responsible for ion conduction).
[0066] In the battery reaction, electrons can quickly pass through the current collector 1 to reach or leave the reaction site, while ions are quickly transmitted through the fibers. The two work together to improve the reaction rate and efficiency of the battery, thereby improving the overall performance of the battery, including rate performance and cycle stability.
[0067] In a preferred embodiment, the active material coating 2 is one of a positive electrode active material coating and a negative electrode active material coating, and the thickness of the active material coating 2 is 10 um to 300 um;
[0068] The active material coating 2 also includes composite active material particles 5, a conductive agent, composite solid electrolyte particles and a binder;
[0069] The conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene and carbon fibers.
[0070] Specifically, the thickness of the positive electrode active material coating layer and the negative electrode active material coating layer may be the same or different, and each independent thickness is 10 um to 300 um, and specifically 100 um to 200 um.
[0071] The positive electrode active material coating comprises positive electrode composite active material particles, positive electrode conductive agent, composite solid electrolyte particles, magnetic composite solid electrolyte fibers 3 and adhesive.
[0072] The negative electrode active material coating comprises negative electrode composite active material particles, negative electrode conductive agent, composite solid electrolyte particles, magnetic composite solid electrolyte fibers 3 and adhesive.
[0073] The positive electrode conductive agent and the negative electrode conductive agent are the same or different and are independent of each other. The positive electrode conductive agent and the negative electrode conductive agent are specifically a mixture of conductive carbon black and carbon nanotubes.
[0074] The positive electrode composite solid electrolyte particles and the negative electrode composite solid electrolyte particles are the same or different, and are independently first type composite solid electrolyte particles 7 and second type composite solid electrolyte particles 9 .
[0075] The adhesive includes at least one of PVDF, PTFE, PVA, and PAA. Taking PVDF as an example, its molecular structure contains fluorine atoms and carbon chains. The high electronegativity of fluorine atoms makes PVDF molecules have a certain polarity, and can interact with other components (such as the surface of active material particles with a certain polarity, electrolyte particles, etc.) through van der Waals forces, hydrogen bonds, etc., to achieve good adhesion.
[0076] PTFE contains a large number of fluorine atoms in its molecular structure, has strong intermolecular forces, excellent chemical stability and low surface energy, which enables it to play a good bonding and stabilizing role in electrode materials.
[0077] PVA molecules contain hydroxyl groups, which can form hydrogen bonds and interact with other substances containing polar groups to enhance the bonding effect.
[0078] The carboxyl groups in the PAA molecule can be combined with other components through hydrogen bonds, ionic bonds, etc., and its molecular chain has a certain flexibility, which can adapt to the volume changes of the electrode material during the charging and discharging process and maintain the stability of the bonding.
[0079] In a preferred embodiment, the composite solid electrolyte particles include first type composite solid electrolyte particles 7 and second type composite solid electrolyte particles 9;
[0080] The magnetic composite solid electrolyte fiber 3 includes a magnetic nanowire 4 and a second type of composite solid electrolyte particles 9 wrapped outside the magnetic nanowire 4, and the weight ratio of the magnetic nanowire 4 to the second type of composite solid electrolyte particles 9 is (70:30) to (90:10);
[0081] The particle size D50 of the magnetic composite solid electrolyte fiber 3 is 10nm to 50nm, and the length of the magnetic composite solid electrolyte fiber 3 is 1um to 200um;
[0082] The magnetic nanowires 4 include at least one of ferrite nanowires, cobalt-based nanowires, nickel-based nanowires, tubular carbon nanofibers, and CaO / α-Fe nanocomposite fibers.
[0083] In a preferred embodiment, the mass ratio of the first type of composite solid electrolyte particles 7 to the second type of composite solid electrolyte particles 9 is (75:25) to (90:10);
[0084] The composite active material particles 5 include active material particles 6 and second type composite solid electrolyte particles 9 wrapped outside the active material particles 6, and the thickness of the second type composite solid electrolyte particles 9 is 10nm to 50nm;
[0085] The active material particles 6 are one of positive electrode active material particles and negative electrode active material particles, and the mass ratio of the positive electrode active material particles to the second type of composite solid electrolyte particles 9 is (93:7) to (97:3);
[0086] The composite active material particles 5 are one of positive composite active material particles and negative composite active material particles, the particle size D50 of the positive composite active material particles is 3.5 um to 5.0 um, and the particle size D50 of the positive active material particles is 2.0 um to 4.0 um;
[0087] The positive electrode composite active material particles include positive electrode active material particles and second type composite solid electrolyte particles 9 coated on the surface;
[0088] The positive electrode active material particles include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, sodium nickel iron manganese copper oxide and Na x At least one of M1[M2(CN)6](0<x<6);
[0089] The negative electrode active material particles include at least one of graphite, silicon, lithium titanate, hard carbon, and soft carbon;
[0090] The first type of composite solid electrolyte particles 7 include inorganic solid electrolyte particles 8 and second type of composite solid electrolyte particles 9 wrapped outside the inorganic solid electrolyte particles 8, and the thickness of the second type of composite solid electrolyte particles 9 is 10nm to 50nm;
[0091] The mass ratio of the inorganic solid electrolyte particles 8 to the second type of composite solid electrolyte particles 9 is (85:15) to (95:5);
[0092] The particle size D50 of the first type of composite solid electrolyte particles 7 is 0.3um to 0.5um, and the particle size D50 of the inorganic solid electrolyte particles 8 is 0.2um to 0.4um;
[0093] The second type of composite solid electrolyte particles 9 include an inorganic electrolyte salt 10 and an organic polymer solid electrolyte 11 wrapped around the inorganic electrolyte salt 10, and the weight ratio of the organic polymer solid electrolyte 11 to the inorganic electrolyte salt 10 is (80:20) to (90:10);
[0094] The particle size D50 of the second type of composite solid electrolyte particles 9 is 0.15 um to 0.30 um.
[0095] Specifically, D50 represents the particle size value corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. That is, the particles are sorted according to the particle size, starting from the smallest particle size, and when the cumulative particle volume (or mass, etc., depending on the measurement method) accounts for 50% of the total particle volume (or mass, etc.), the corresponding particle size is D50.
[0096] The positive electrode active material particles specifically include at least one of LiCoO2, LiNi8Co1Mn1O2, NaNi3Fe3Mn3Cu1O2, and Na2Fe[Fe(CN)6].
[0097] The organic polymer solid electrolyte 11 includes at least one of PEO, PMMA, PVDF-HFP, and HNBR.
[0098] The inorganic electrolyte salt 10 includes at least one of LiPF6, NaPF6, LiBF4, NaBF4, NaTFSI, LiTFSI, LiDFOB, and NaDFOB.
[0099] The inorganic solid electrolyte particles 8 are inorganic oxide solid electrolytes or sulfide solid electrolytes or a mixture of the two electrolytes. The inorganic solid electrolyte particles 8 are specifically Li7La3Zr2O 12 , Li 1+x Al x Ti 2-x (PO4)3, LiTaO3, LiNbO3, Na3Zr2Si2PO 12 , Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one of .
[0100] A method for preparing an all-solid-state battery pole piece, for preparing an all-solid-state battery pole piece, referring to Figure 6 ,include,
[0101] Step S1, spraying and cooling the prefabricated molten slurry to obtain the second type of composite solid electrolyte particles 9;
[0102] Step S2, adding active material particles 6 to the prefabricated molten slurry, spraying and cooling after mixing, to form composite active material particles 5;
[0103] Step S3, adding inorganic solid electrolyte particles 8 to the prefabricated molten slurry, spraying and cooling after mixing, to form first type composite solid electrolyte particles 7;
[0104] Step S4, adding magnetic nanowires 4 to the prefabricated molten slurry, spraying after mixing, and stretching and refining under the action of electric field force to form magnetic composite solid electrolyte fibers 3;
[0105] Step S5, after mixing the second type of composite solid electrolyte particles 9, the composite active material particles 5, the first type of composite solid electrolyte particles 7, the conductive agent and the adhesive according to the first mass ratio, adding the magnetic composite solid electrolyte fiber 3, mixing again to obtain a mixed material, spraying the mixed material on the substrate, and introducing an electric field to obtain an active material coating 2;
[0106] Step S6, pressing the current collector 1 and the active material coating 2 at a first temperature and a first pressure by a multi-roll hot pressing device to obtain an all-solid-state battery electrode.
[0107] Specifically, the present invention also provides a method for preparing an all-solid-state battery electrode sheet. The magnetic composite solid electrolyte fiber 3 serves as a long-range ion conductor, which improves the ion conductivity of the electrode sheet. In particular, when the electrode expands during the battery charging and discharging process, the long-range ion conductor can also ensure the ion conductivity of the electrode, thereby improving the cycle performance of the all-solid-state battery.
[0108] In a preferred embodiment, the prefabricated molten slurry in step S1 to step S4 is obtained by melting the organic polymer solid electrolyte 11 in a vacuum melting machine, and then adding the inorganic electrolyte salt 10 and stirring.
[0109] Specifically, in Example 1, the preparation process of the second type of composite solid electrolyte particles 9 includes:
[0110] Add the organic polymer solid electrolyte 11 into a high-temperature vacuum melting machine, and stir it for 60 minutes at 80±5°C and 25Hz to fully melt it;
[0111] Add 10% inorganic electrolyte salt, and stir at 80±5°C and 15Hz for 30min to fully mix to form a molten slurry;
[0112] Using a high-pressure spray device to spray and cool the molten slurry into second-type composite solid electrolyte particles 9;
[0113] Wherein, the organic polymer solid electrolyte 11 is PEO;
[0114] The inorganic electrolyte salt 10 is LiBF4;
[0115] The D50 of the second type of composite solid electrolyte particles 9 is 0.20±0.05um;
[0116] The weight ratio of the second type of composite solid electrolyte particles 9 to the inorganic electrolyte salt 10 is 85:15.
[0117] The preparation process of the composite active material particles 5 includes:
[0118] Add the organic polymer solid electrolyte 11 into a high-temperature vacuum mixer and stir for 60 minutes at 80±5°C and 25Hz to fully melt it;
[0119] Add 10% inorganic electrolyte salt, and stir at 80±5°C and 15Hz for 30min to fully mix to form a molten slurry;
[0120] Then add (positive electrode or negative electrode) active material particles and mix thoroughly; use high-pressure spray equipment to spray the molten slurry and cool it into (positive electrode or negative electrode) active material particles 6 to obtain composite active material particles 5;
[0121] The organic polymer solid electrolyte 11 is PEO;
[0122] The inorganic electrolyte salt 10 is LiBF4;
[0123] The positive electrode active material particles are lithium nickel cobalt manganese oxide;
[0124] The particle size D50 of lithium nickel cobalt manganese oxide particles is 2.8±0.2um;
[0125] The D50 of the first type of composite active material particles is 3.8±0.15um;
[0126] The surface coating thickness of the second type of composite solid electrolyte particles 9 is 20nm to 30nm;
[0127] The ratio of lithium nickel cobalt manganese oxide to the second type of composite solid electrolyte particles 9 is 95:5.
[0128] The preparation process of the first type of composite solid electrolyte particles 7 includes:
[0129] Add the organic polymer solid electrolyte 11 into a high-temperature vacuum melting machine, and stir for 60 minutes at 80±5°C and 25Hz to fully melt it;
[0130] Add 10% inorganic electrolyte salt, and stir at 80±5°C and 15Hz for 30min to fully mix to form a molten slurry;
[0131] Then add the inorganic solid electrolyte particles 8 and mix thoroughly;
[0132] Using a high-pressure spray device to spray and cool the molten slurry into first-type composite solid electrolyte particles 7;
[0133] The organic polymer solid electrolyte 11 is PEO;
[0134] The inorganic electrolyte salt 10 is LiBF4;
[0135] The inorganic solid electrolyte particles 8 are Li2S-P2S5-LiCl;
[0136] The particle size D50 of Li2S-P2S5-LiCl is 0.25±0.05um;
[0137] The D50 of the first type of composite solid electrolyte particles 7 is 0.4 ± 0.05 μm;
[0138] The surface coating thickness of the second type of composite solid electrolyte particles 9 is 10nm to 30nm;
[0139] The ratio of Li2S-P2S5-LiCl to the second type of composite solid electrolyte particles 9 is 90:10.
[0140] The preparation process of the magnetic composite solid electrolyte fiber 3 includes:
[0141] Add the organic polymer solid electrolyte 11 into a high-temperature vacuum melting machine, and stir for 60 minutes at 80±5°C and 25Hz to fully melt it;
[0142] Add 10% inorganic electrolyte salt, and stir at 80±5°C and 15Hz for 30min to fully mix to form a molten slurry;
[0143] Then add magnetic nanowire 4 and mix thoroughly;
[0144] The molten slurry is sprayed by a high-pressure spray device, and under the action of the electric field force, the magnetic nanowires 4 coated with the polymer electrolyte and the inorganic electrolyte salt 10 are stretched and thinned during the flight, and finally deposited on the receiver to form the magnetic composite solid electrolyte fiber 3;
[0145] The organic polymer solid electrolyte 11 is PEO;
[0146] The inorganic electrolyte salt 10 is LiBF4;
[0147] The magnetic nanowire 4 is a ferrite (Fe3O4) nanowire;
[0148] The diameter of the magnetic composite solid electrolyte fiber 3 is 20nm-30nm, and the length is 100um-150um;
[0149] The ratio of the magnetic nanowires 4 to the second type of composite solid electrolyte particles 9 is 80:20.
[0150] The preparation process of the active material coating 2 includes:
[0151] The composite active material particles 5, the composite solid electrolyte particles, the conductive agent, and the adhesive are uniformly mixed according to a certain ratio, and then the adhesive is fiberized and granulated so that the adhesive fibers fully contact and cover the composite active material particles 5 and the composite solid electrolyte particles;
[0152] Add the magnetic composite solid electrolyte fiber 3 into the vacuum mixing equipment, so that the magnetic composite solid electrolyte fiber 3 and the composite active material particles 5, the composite solid electrolyte particles and other materials are fully mixed, and use the powder spraying equipment to evenly spray the above mixed materials onto the PET substrate. In the spraying process, an electric field is introduced so that the magnetic composite solid electrolyte fiber 3 in the mixed material is arranged at an angle perpendicular to the PET substrate;
[0153] The composite active material particles 5 coated with the adhesive fiber, the composite solid electrolyte particles, the magnetic composite solid electrolyte fiber 3, the conductive agent and the adhesive are made into the active material coating 2 by a press film-forming device;
[0154] The adhesive is PTFE;
[0155] The thickness of the active material coating 2 is 200 μm;
[0156] The ratio of the composite active material particles 5, the composite solid electrolyte particles, the magnetic composite solid electrolyte fibers 3, the conductive agent, and the adhesive is 85:8:3:2:2.
[0157] In a preferred embodiment, the first mass ratio in step S5 is (80:10:5:2:3) to (90:6:2:1:1).
[0158] Specifically, the composite active material particles 5 are the core of the electrochemical reaction of the battery, and a high content of the composite active material particles 5 ensures the energy supply capacity of the battery.
[0159] The composite solid electrolyte particles are in close contact with the active material particles, and their reasonable mass ratio ensures that ions can migrate quickly between the active material particles. There are interactions between different types of active materials and electrolyte particles.
[0160] For example, the chemical properties of the surface of active material particles will affect their interfacial compatibility with electrolyte particles. A suitable mass ratio can form good interfacial contact between them, reduce the interfacial resistance of ion transport, and improve ion conduction efficiency.
[0161] The proportion of the magnetic composite solid electrolyte fiber 3 can ensure its function as a long-range ion conductor without affecting the proportion and function of other components due to excessive content.
[0162] Under the action of the electric field force, the vertically arranged structure of the magnetic composite solid electrolyte fiber 3 cooperates with other components to optimize the ion conduction path.
[0163] The presence of an appropriate amount of conductive agent in the mass ratio can form an effective electron conduction network between the active material particles and promote the rapid transmission of electrons.
[0164] The binder fills the gaps between the particles through interaction with other components, bonding the components together and enhancing the structural integrity of the electrode.
[0165] For example, the nanostructure of the conductive agent can form conductive contact points with the surface of the active material particles, while the binder molecules can wrap around the particle surface and the conductive agent to stabilize their relative positions.
[0166] The mass ratio directly affects the microstructure of the electrode material. When the composite active material particles 5, the composite solid electrolyte particles, the magnetic composite solid electrolyte fibers 3, the conductive agent and the adhesive are mixed in a suitable mass ratio, they form a specific arrangement and contact mode on a microscopic scale.
[0167] For example, the appropriate mass ratio can make the composite solid electrolyte particles evenly distributed between the active material particles, forming a continuous ion conduction channel; the conductive network formed by the conductive agent can be well connected with the active material particles, facilitating the transmission of electrons. This microstructure optimization is directly reflected in the macroscopic performance, such as reducing battery impedance, improving rate performance and energy density, etc.
[0168] Adjustment of the mass ratio changes the overall performance of the battery electrode, thereby enabling it to adapt to different application requirements.
[0169] In applications requiring high energy density, a higher active material content and optimized ion and electron conductivity (achieved through a reasonable mass ratio) can provide sufficient power output.
[0170] In applications with high requirements for cycle life, a stable electrode microstructure can resist volume changes and structural damage during multiple charge and discharge processes, thus extending the service life of the battery.
[0171] The change in mass ratio affects the microstructure, ultimately achieving the adaptability of macroscopic performance to different application scenarios.
[0172] In a preferred embodiment, in step S6, the first temperature is 45°C to 100°C, and the first pressure is 5MPa to 100MPa;
[0173] In step S6, the multi-roller hot pressing device is provided with n pressing rollers along the first direction, wherein the temperature of the n / 2th pressing roller is the highest, the temperatures of the pressing rollers before the n / 2th pressing roller are successively increased along the first direction, and the temperatures of the pressing rollers after the n / 2th pressing roller are successively decreased along the first direction;
[0174] The pressure of the n pressure rollers gradually increases along the first direction;
[0175] Where n∈[6,12] and n is divisible by 2.
[0176] Specifically, in Example 1, the preparation process of the low-porosity high-performance all-solid-state battery electrode includes:
[0177] Using a multi-roll hot pressing device to press the current collector 1 and the active material coating 2 into a low-tortuosity, low-impedance all-solid-state battery pole piece under certain temperature and pressure conditions;
[0178] In this embodiment, the number of pressure rollers is 8;
[0179] The temperature range of the pressure rollers is 50℃~110℃, the highest temperature is the 4th roller, rollers 2 to 4, the temperature of each roller increases by 20℃, and the temperature of rollers 5 to 8 gradually decreases, each roller decreases by 15℃;
[0180] The pressure range is 5MPa~110MPa;
[0181] The pressure increases gradually from the first roller to the last roller, 5MPa for roller No. 1, 20MPa for roller No. 2, and the pressure of each roller increases by 15MPa until the pressure of roller No. 8 reaches 110MPa.
[0182] After the low-impedance all-solid-state battery pole piece is pressed by a multi-roll hot pressing device, the obtained all-solid-state positive electrode piece and all-solid-state negative electrode piece are used together with the purchased all-solid-state electrolyte membrane to form a 2Ah all-solid-state battery;
[0183] The solid-state battery was subjected to 50% SOC-DCR, rate (1C), and 0.5C-100% DOD cycle tests, and the results are shown in Table 1 (test data of each group of embodiments and comparative examples).
[0184] Embodiment 2:
[0185] The difference from Example 1 is that the organic polymer solid electrolyte 11 used in this example is PMMA, and the rest is the same as Example 1.
[0186] Embodiment 3:
[0187] The difference from Example 1 is that the inorganic electrolyte salt 10 used in the second type of composite solid electrolyte particles 9 in this example is LiPF6, and the rest is the same as Example 1.
[0188] Embodiment 4:
[0189] Different from Example 1, the inorganic electrolyte salt 10 used in this example is NaBF4, and the corresponding active material is NaNi3Fe3Mn3Cu1O2. The rest is the same as Example 1.
[0190] Embodiment 5:
[0191] Different from Example 1, the active material used in this example is hard carbon, the battery electrode is made of negative electrode, and the rest is the same as Example 1.
[0192] Embodiment 6:
[0193] Different from Example 1, the weight ratio of the organic polymer solid electrolyte 11 to the inorganic electrolyte salt 10 in the second type of composite solid electrolyte particles 9 in this embodiment is 90:10; the rest is the same as Example 1.
[0194] Embodiment 7:
[0195] The difference from Example 1 is that the particle size of the second type of composite solid electrolyte particles 9 in this embodiment is: D50: 0.28±0.05 um; the rest is the same as Example 1.
[0196] Embodiment 8:
[0197] Different from Example 1, the active material particles in this embodiment: D50: 3.5±0.2 um;
[0198] Composite active material particles 5: D50: 4.2±0.15 um; the rest is the same as Example 1.
[0199] Embodiment 9:
[0200] The difference from Example 1 is that in this embodiment, the particle size of the first type of inorganic solid electrolyte particles is: D50: 0.3±0.05um; the first type of composite solid electrolyte particles 7: D50: 0.45±0.05um; the rest is the same as Example 1.
[0201] Embodiment 10:
[0202] Different from Example 1, in this embodiment, the ratio of the first type of inorganic solid electrolyte particles to the second type of composite solid electrolyte particles 9 is 85:15; the rest is the same as Example 1.
[0203] Embodiment 11:
[0204] Different from Example 1, the ratio of composite active material particles 5, composite solid electrolyte particles, magnetic composite solid electrolyte fibers 3, conductive agent, and adhesive in this example is 80:10:5:2:3; the rest is the same as Example 1.
[0205] Embodiment 12:
[0206] The difference from the first embodiment is that the material of the magnetic nanowire 4 in this embodiment is nickel-based nanowire; the rest is the same as the first embodiment.
[0207] Embodiment 13:
[0208] The difference from Example 1 is that the magnetic composite solid electrolyte fiber 3 in this example has a diameter of 30nm-50nm and a length of 1um-100um; the rest is the same as Example 1.
[0209] Comparative Example 1:
[0210] Different from Example 1, the active material and the inorganic solid electrolyte in this comparative example are not coated with the second type of composite solid electrolyte particles 9, and the other proportions and processes are the same as those in Example 1.
[0211] Comparative Example 2:
[0212] The difference from Example 1 is that no magnetic composite solid electrolyte fiber 3 is added in this comparative example, and other proportions and processes are the same as those in Example 1.
[0213] Comparative Example 3:
[0214] Different from Example 1, the magnetic nanowires 4 in this comparative example are not coated with the second type of composite solid electrolyte particles 9 , and other proportions and processes are the same as those in Example 1.
[0215] Comparative Example 4:
[0216] The difference from Example 1 is that the magnetic composite solid electrolyte fiber 3 in this comparative example has a diameter of 100nm-200nm and a length of 1um-10um, and other proportions and processes are the same as those in Example 1.
[0217] Comparative Example 5:
[0218] The difference from Example 1 is that the magnetic composite solid electrolyte fiber 3 in this comparative example has a diameter of 100nm-200nm and a length of 500um-1000um, and other proportions and processes are the same as those in Example 1.
[0219] Comparative Example 6:
[0220] Different from Example 1, the weight ratio of the magnetic nanowires 4 to the second type of composite solid electrolyte particles 9 in this comparative example is 60:40, and other ratios and processes are the same as those in Example 1.
[0221] Comparative Example 7:
[0222] Different from Example 1, the weight ratio of the magnetic nanowires 4 to the second type of composite solid electrolyte particles 9 in this comparative example is 95:5, and other ratios and processes are the same as those in Example 1.
[0223]
[0224] It can be seen from the above results that the solid-state battery made using the low-tortuosity and low-impedance all-solid-state battery electrode provided by the present invention has low impedance and significantly improved rate and cycle performance.
[0225] The low-tortuosity, low-impedance all-solid-state battery pole piece provided by the present invention can reduce the transmission path of lithium / sodium ions, thereby reducing the internal resistance of the battery and improving the charging and discharging efficiency and power density. From the perspective of electrode design, the problem of long ion transmission distance and increased internal resistance under high surface density design is solved, thereby improving the performance and application prospects of all-solid-state batteries.
[0226] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.
Claims
1. An all-solid-state battery pole piece, characterized in that: include, current collector; An active material coating is covered on the upper surface and the lower surface of the current collector, wherein the active material coating comprises magnetic composite solid electrolyte fibers, and the arrangement direction of the magnetic composite solid electrolyte fibers is perpendicular to the current collector.
2. The all-solid-state battery pole piece according to claim 1, characterized in that: The current collector is one of a positive electrode current collector and a negative electrode current collector; The positive electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil; The thickness of the positive electrode current collector is 4um to 20um; The negative electrode current collector is one of the aluminum foil, the microporous aluminum foil, the corroded aluminum foil, the composite aluminum foil, the copper foil, the microporous copper foil, the corroded copper foil, the composite copper foil, the steel foil, the corroded steel foil and the microporous steel foil; The thickness of the negative electrode current collector is 4 um to 15 um.
3. The all-solid-state battery pole piece according to claim 1, characterized in that: The active material coating is one of a positive electrode active material coating and a negative electrode active material coating, and the thickness of the active material coating is 10 um to 300 um; The active material coating also includes composite active material particles, a conductive agent, composite solid electrolyte particles and a binder; The conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene and carbon fibers.
4. The all-solid-state battery pole piece according to claim 3, characterized in that: The composite solid electrolyte particles include first-type composite solid electrolyte particles and second-type composite solid electrolyte particles; The magnetic composite solid electrolyte fiber comprises a magnetic nanowire and the second type of composite solid electrolyte particles wrapped outside the magnetic nanowire, and the weight ratio of the magnetic nanowire to the second type of composite solid electrolyte particles is (70:30) to (90:10); The particle size D50 of the magnetic composite solid electrolyte fiber is 10nm to 50nm, and the length of the magnetic composite solid electrolyte fiber is 1um to 200um; The magnetic nanowires include at least one of ferrite nanowires, cobalt-based nanowires, nickel-based nanowires, tubular carbon nanofibers, and CaO / α-Fe nanocomposite fibers.
5. The all-solid-state battery pole piece according to claim 4, characterized in that: The mass ratio of the first type of composite solid electrolyte particles to the second type of composite solid electrolyte particles is (75:25) to (90:10); The composite active material particles include active material particles and the second type of composite solid electrolyte particles wrapped outside the active material particles, and the thickness of the second type of composite solid electrolyte particles is 10nm to 50nm; The active material particles are one of positive electrode active material particles and negative electrode active material particles, and the mass ratio of the positive electrode active material particles to the second type of composite solid electrolyte particles is (93:7) to (97:3); The composite active material particles are one of positive electrode composite active material particles and negative electrode composite active material particles, the particle size D50 of the positive electrode composite active material particles is 3.5um to 5.0um, and the particle size D50 of the positive electrode active material particles is 2.0um to 4.0um; The positive electrode active material particles include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, sodium nickel iron manganese copper oxide and Na x At least one of M1[M2(CN)6](0<x<6); The negative electrode active material particles include at least one of graphite, silicon, lithium titanate, hard carbon, and soft carbon; The first type of composite solid electrolyte particles include inorganic solid electrolyte particles and the second type of composite solid electrolyte particles wrapped outside the inorganic solid electrolyte particles, and the thickness of the second type of composite solid electrolyte particles is 10nm to 50nm; The mass ratio of the inorganic solid electrolyte particles to the second type of composite solid electrolyte particles is (85:15) to (95:5); The particle size D50 of the first type of composite solid electrolyte particles is 0.3um to 0.5um, and the particle size D50 of the inorganic solid electrolyte particles is 0.2um to 0.4um; The second type of composite solid electrolyte particles comprises an inorganic electrolyte salt and an organic polymer solid electrolyte wrapped outside the inorganic electrolyte salt, and the weight ratio of the organic polymer solid electrolyte to the inorganic electrolyte salt is (80:20) to (90:10); The particle size D50 of the second type of composite solid electrolyte particles is 0.15um to 0.30um.
6. A method for preparing an all-solid-state battery electrode, characterized in that: For preparing the all-solid-state battery pole piece according to any one of claims 1 to 5, comprising: Step S1, spraying and cooling the prefabricated molten slurry to obtain the second type of composite solid electrolyte particles; Step S2, adding active material particles to the prefabricated molten slurry, spraying and cooling after mixing to form composite active material particles; Step S3, adding inorganic solid electrolyte particles to the prefabricated molten slurry, spraying and cooling after mixing, to form first type composite solid electrolyte particles; Step S4, adding magnetic nanowires to the prefabricated molten slurry, spraying after mixing, and stretching and refining under the action of electric field force to form the magnetic composite solid electrolyte fiber; Step S5, mixing the second type of composite solid electrolyte particles, the composite active material particles, the first type of composite solid electrolyte particles, the conductive agent and the adhesive according to a first mass ratio, adding the magnetic composite solid electrolyte fiber, mixing again to obtain a mixed material, spraying the mixed material on a substrate, and introducing an electric field to obtain the active material coating; Step S6, pressing the current collector and the active material coating at a first temperature and a first pressure by a multi-roll hot pressing device to obtain the all-solid-state battery electrode.
7. The method for preparing an all-solid-state battery pole piece according to claim 6, characterized in that: The prefabricated molten slurry in step S1 to step S4 is obtained by melting an organic polymer solid electrolyte in a vacuum melting machine, and then adding an inorganic electrolyte salt and stirring.
8. The method for preparing an all-solid-state battery pole piece according to claim 6, characterized in that: In step S5, the first mass ratio is (80:10:5:2:3) to (90:6:2:1:1).
9. The method for preparing an all-solid-state battery pole piece according to claim 6, characterized in that: In step S6, the first temperature is 45°C to 100°C, and the first pressure is 5MPa to 100MPa.
10. The method for preparing an all-solid-state battery pole piece according to claim 6, characterized in that: In step S6, the multi-roller hot pressing device is provided with n pressing rollers along the first direction, wherein the temperature of the n / 2th pressing roller is the highest, the temperature of the pressing rollers before the n / 2th pressing roller increases successively along the first direction, and the temperature of the pressing rollers after the n / 2th pressing roller decreases successively along the first direction; The pressure of the n pressure rollers gradually increases along the first direction; Where n∈[6,12] and n is divisible by 2.